Determination of dose distributions and dose rates in the gamma knife - (:unkn) unknown (My University, 2003)
PURPOSE: To measure the dose parameters of the Leksell gamma knife unit and compare them with the treatment planning data. MATERIALS AND METHODS: The dose distributions taken from treatment planning computer were confirmed with film dosimetry using a spherical uniform density polystyrene phantom. The dose rate measurements were made by using a 0.125 cc ion chamber and the spherical phantom for 4, 8, 14 and 18 mm helmets. The dose rate measurements were compared with the estimates given by the manufacturer. RESULTS: The dose distributions obtained by film dosimetry were in agreement with those taken from the treatment planning computer only for the 70% and 50% isodose line. The results of dose rate measurement showed that the 0.125 cc ion chamber was suitable only for 18 and 14 mm helmets. Conversely, it was not suitable for 8 and 4 mm helmets. CONCLUSION: This study showed that both computergenerated treatment plans and film densitometry estimates provided similar dose distributions without special beam blocking.